Health education on clean and healthy living behaviors and introduction to drug logos at MI Assalafiyah, Bode Lor Village - Hidayati, Nur Rahmi; Indawati, Iin; Fatonah, Ani; Achelia, Elvanka Putri; Chaniago, Adhilla Kristina; Nabila, Syakira Putri (Community Empowerment, 2025)
Health education for school-age children is a crucial step in shaping clean and healthy living habits. One aspect that is often overlooked is the classification of medicines based on the logos displayed on their packaging. This community service activity aims to educate students of MI Assalafiyah Bode Lor on clean and healthy living behaviors, as well as medication logos. The methods used in this activity include health counseling, poster-based education, and evaluation. The results show a 34% increase in knowledge regarding clean and healthy living behaviors and medication logos. With better understanding, students can become more independent in maintaining their personal health and identifying the appropriate type of medicine based on the packaging logo, fostering a healthier and more informed younger generation.